PENGARUH PENGALAMAN PELANGGAN DAN KEPERCAYAAN TERHADAP NIAT BELI ULANG MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Hendri Rahmayani Asri; Ekaning Setyarini; Hantoro Arief Gisijanto; Nenik Diah Hartanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of customer experience and trust on customer repurchase intentions of products sold at Lazada mediated by customer satisfaction. Repurchase intention is a post-purchase action caused by the satisfaction felt by consumers for products that have been previously purchased or consumed. Repurchase intention can be understood with satisfaction and trust, as consumers tend to rely on their experience after the initial transaction.The data collection method used in this research is literature study and field study. The data used in this research is primary data. The variables used in this study are customer experience and trust as independent variables, while repurchase intention as the dependent variable and customer satisfaction as the mediating variable. The sample in this study using purposive sampling technique. The data in this study were processed using AMOS. Based on the results of this study, it shows that the variables of customer experience and trust have a positive effect on customer satisfaction. Customer experience variables have no effect on customer repurchase intentions. The trust variable has a positive effect on customer repurchase intention. Customer satisfaction variables have a positive effect on customer repurchase intentions. Customer satisfaction variables can mediate the indirect effect of customer experience and trust in Lazada.coc.id customer repurchase intentions. Lazada can continue to build customer trust so that customer repurchase intentions remain high. Lazada as an online sales website should be able to guarantee customer safety in making purchases and online payments so that buyer satisfaction increases.